Pengaruh Model Pembelajaran Discovery Learning untuk Meningkatkan Pemahaman Konsep IPA Siswa SMP Satrya Budi Perdagangan - Siahaan, Fine Eirene; Sihotang, Cintia (Jurnal Simki Pedagogia, 2023)
This study aims to determine the effect of Discovery Learning models in improving the understanding of the science concepts of the students of SMP Satrya Budi Trade. In this study the method used is Quasi Experimental Design with the research design, Nonequivalent Control Group Design. In this study using two classes. The two classes are the control class and the experimental class. The control class will use the conventional learning model while the experimental class will use the discovery learning learning model. The sample in this study was Class VII of the Satrya Budi Middle School, each of which consisted of 20 students. The research instrument used in this study was a test of student learning outcomes in the form of pretest and posttest to measure the understanding of student concepts in the cognitive domain. Based on the results of the statistical test research, the t-test, namely (1) the difference in the student's learning outcomes difference obtained the value of tcount of 4.503, the calculation uses the t-t-test at the significance level (α) = 0.05, obtained THitung> ttable that is 4,503> 2,024, so that the zero hypothesis (H0) is rejected and (H1) is accepted, so it can be concluded that there is the influence of the Discovery Learning learning model to improve the understanding of the science concepts of the Satrya Budi Perdagangan Middle School students, (2) In accordance with the research that has been conducted and the results that have been obtained by the researcher, the research conducted using the Discovery Learning model to improve the understanding of the concept of science in the Satrya Budi Trade Middle School can be declared well with the final results of the study received an average value of 80%.